Rationality for mortals : how people cope with uncertainty - Gigerenzer, Gerd (Evolution and cognition, 2010)
This volume collects Gigerenzer's recent articles on the psychology of rationality. This volume should appeal, like the earlier volumes, to a broad mixture of cognitive psychologists, philosophers, economists, and others who study decision making.